The Beneficial Effect of Yoghurt Containing Lactobacillus Rhamnosus on Caries Prevention in Children With Diabetes Mellitus Type 1 - Lovrić, Jovana; Vukajlović, Dijana; Ćulibrk, Branka; Dimitrijević, Pava; Rađan Gajić, Milena; Adamović, Tijana; Janković, Ognjenka; Bukara Radujković, Gordana; Arlov, Goran; Dolić, Olivera (Scripta Medica, 2022)
Background / Aim: Children with type 1 diabetes mellitus are thought to have an increased risk of caries. This study aimed to examine the short-term effect (sixty days long) of commercially available yoghurt consumption containing the Lactobacillus rhamnosus probiotic culture (LGG yoghurt) on the oral Streptococcus mutans count and saliva buffer capacity in children with type 1 diabetes mellitus. Methods: Children were divided into two groups: the experimental group and the placebo group. Both groups consisted of 50 (N = 50) children with juvenile diabetes, aged 10-15 years, with controlled glucose levels and irregular oral hygiene. At the first examination, every child was evaluated for the caries risk. A sample of unstimulated saliva before yoghurt consumption and after washout of the teeth was inspected for S mutans count. The samples were tested for Saliva buffer capacity (Saliva-Check Buffer Testing Mat GC America). The same procedure was repeated after 14 days, 30 days and 60 days after the treatment with probiotic yoghurt. Results: The results showed decreased number of S mutans colonies at the 60-day control examination in the probiotic group. The study also proved a significant increase in saliva buffer capacity in both groups after 60 days. Conclusion: It could be concluded that daily consumption of LGG yoghurt can improve caries prevention in children with diabetes mellitus type I.